Bueno Alonso, Jorge Luis & Laura Torrado Mariñas 2012: Judith del Cotton Vitellius A. XV ff . 202r–209v: Texto, estudio y traducción - Valdés Miyares, Rubén (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen